Atrial Back Wall Support to Facilitate Antegrade Closure of Complex Mitral Paravalvular Leaks - Joshua Rezkalla, MD; Mohamad Alkhouli, MD (JACC: Case Reports, 2023)
Transapical puncture for transcatheter treatment of mitral-paravalvular leak (PVL) is associated with increased risks even when the apical tract is closed with vascular plugs. A novel technique that leverages back wall support from the right or left atrium can be used to facilitate transcatheter closure of mitral PVL through an antegrade approach. (Level of Difficulty: Advanced.)